Incident subjective cognitive decline does not predict mortality in the elderly: results from the longitudinal German study on Ageing, Cognition, and Dementia (AgeCoDe) - Röhr, Susanne; Weyerer, Siegfried (PLOS ONE, 2016)
Objective Subjective cognitive decline (SCD) might represent the first symptomatic representation of Alzheimer’s disease (AD), which is associated with increased mortality. Only few studies, however, have analyzed the association of SCD and mortality, and if so, based on prevalent cases. Thus, we investigated incident SCD in memory and mortality. Methods Data were derived from the German AgeCoDe study, a prospective longitudinal study on the epidemiology of mild cognitive impairment (MCI) and dementia in primary care patients over 75 years covering an observation period of 7.5 years. We used univariate and multivariate Cox regression analyses to examine the relationship of SCD and mortality. Further, we estimated survival times by the Kaplan Meier method and case-fatality rates with regard to SCD. Results Among 971 individuals without objective cognitive impairment, 233 (24.0%) incidentally expressed SCD at follow-up I. Incident SCD was not significantly associated with increased mortality in the univariate (HR = 1.0, 95% confidence interval = 0.8-1.3, p = .90) as well as in the multivariate analysis (HR = 0.9, 95% confidence interval = 0.7-1.2, p = .40). The same applied for SCD in relation to concerns. Mean survival time with SCD was 8.0 years (SD = 0.1) after onset. Conclusion Incident SCD in memory in individuals with unimpaired cognitive performance does not predict mortality. The main reason might be that SCD does not ultimately lead into future cognitive decline in any case. However, as prevalence studies suggest, subjectively perceived decline in non-memory cognitive domains might be associated with increased mortality. Future studies may address mortality in such other cognitive domains of SCD in incident cases.